1972
DOI: 10.1128/jb.112.2.682-689.1972
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Suppression of Methicillin Resistance in Staphylococcus aureus by Mutant Noninducible Penicillinase Plasmids

Abstract: Methicillin (intrinsic) resistance of Staphylococcus aureus was suppressed almost completely by regulatory gene (penIl) mutations of penicillinase plasmids that made penicillinase production strictly noninducible. Methicillin resistance was restored by secondary regulatory gene mutations that altered the noninducible phenotype or by complementation with a compatible plasmid that did not bear the noninducible mutation. No evidence was obtained for genetic linkage between a penicillinase plasmid and the gene for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…␤-Lactamase regulatory genes may affect the expression of resistance. Mutations altering the inducibility of ␤-lactamase have been associated with reduced (i.e., heterogeneous) expression of methicillin resistance (24). Inactivation of blaR1 can produce heterogeneous resistance, presumably by the unopposed repressor activity of BlaI (57).…”
Section: Factors Affecting Resistance Phenotypementioning
confidence: 99%
“…␤-Lactamase regulatory genes may affect the expression of resistance. Mutations altering the inducibility of ␤-lactamase have been associated with reduced (i.e., heterogeneous) expression of methicillin resistance (24). Inactivation of blaR1 can produce heterogeneous resistance, presumably by the unopposed repressor activity of BlaI (57).…”
Section: Factors Affecting Resistance Phenotypementioning
confidence: 99%
“…Either the physical binding of the penicillin itself or perhaps an effect of penicillin in inhibiting peptidoglycan synthesis leads to transfer of information to the cytoplasm and activation of penicillinase synthesis. Although the entire receptor-transmitter complex might be components of the penicillinase system, another possibility is that some genetic elements involved in control of cell wall synthesis may also be involved in regulation of penicillinase production (37,38).…”
Section: Control Of Cell Wall Synthesismentioning
confidence: 99%
“…For example, recipient effectiveness for transduction of mec requires the presence of either a chromosomal or a plasmid determinant for beta-lactamase production and efficiency of transfer is lower in the presence of beta-lactamase inhibitor (38,39,148). Expression of resistance can be suppressed by mutant-noninducible penicillinase plasmids (37). Recipient effectiveness for mec in Staphylococcus epidermidis partly depends on the presence of the determinant for mercury resistance (19).…”
Section: Other Factorsmentioning
confidence: 99%
“…Genetic determinants physically distinct from mec can alter expression of resistance. The first indication that markers not linked to mec could alter expres-sion of methicillin resistance came from the studies of Cohen and colleagues (37). They found that methicillin resistance could be suppressed by mutations in regulatory genes of inducible penicillinase plasmids.…”
Section: Other Factorsmentioning
confidence: 99%